Muslim Studies in a Christian Theological School: The Muslim Studies Program at Emmanuel College in Toronto - Toulouse, Mark G. (Toronto journal of theology, 2012)
This essay examines the development of a Muslim Studies program within Emmanuel College, a Canadian Christian theological school. The program has grown from a desire within the college to explore meaningfully the diversity associated with its social location in downtown Toronto and to participate responsibly in the important work of inter-religious dialogue. The story of the program's development is placed within an analysis of at least three areas offering challenges to the effort. Faculty members face significant obstacles in reshaping a curriculum within theological education that can address contemporary contexts of both Church and culture in a manner that includes intentional engagement with religious diversity. Within Christian history, a wide variety of methodological approaches have been developed to understand the nature of religious diversity in relation to Christianity. Each offers its own challenges to attempts to shape responsible encounters between Christianity and other world religions. Finally, the rich diversity within Islam existing within the social context of Toronto creates interesting challenges for a program in Muslim Studies intending to take expressions of religious faith seriously. The essay also examines wide-ranging rationales for why a Christian theological school would attempt to face these challenges in order to begin a program designed to provide educational opportunities for Muslims. In the final pages, the three major components of the program are described.